Don’t mind the gap: reframing the Perren strain rule for fracture healing using insights from virtual mechanical testing - Maham Tanveer; Karina Klein; Brigitte von Rechenberg; Salim Darwiche; Hannah L. Dailey (Bone & Joint Research)
Aims: The “2 to 10% strain rule” for fracture healing has been widely interpreted to mean that interfragmentary strain greater than 10% predisposes a fracture to nonunion. This interpretation focuses on the gap-closing strain (axial micromotion divided by gap size), ignoring the region around the gap where osteogenesis typically initiates. The aim of this study was to measure gap-closing and 3D interfragmentary strains in plated ovine osteotomies and associate local strain conditions with callus mineralization. Methods: MicroCT scans of eight female sheep with plated mid-shaft tibial osteotomies were used to create image-based finite element models. Virtual mechanical testing was used to compute postoperative gap-closing and 3D continuum strains representing compression (volumetric strain) and shear deformation (distortional strain). Callus mineralization was measured in zones in and around the osteotomy gap. Results: Gap-closing strains averaged 51% (mean) at the far cortex. Peak compressive volumetric strain averaged 32% and only a small tissue volume (average 0.3 cm3) within the gap experienced compressive strains > 10%. Distortional strains were much higher and more widespread, peaking at a mean of 115%, with a mean of 3.3 cm3 of tissue in and around the osteotomy experiencing distortional strains > 10%. Callus mineralization initiated outside the high-strain gap and was significantly lower within the fracture gap compared to around it at nine weeks. Conclusion: Ovine osteotomies can heal with high gap strains (> 10%) dominated by shear conditions. High gap strain appears to be a transient local limiter of osteogenesis, not a global inhibitor of secondary fracture repair. Cite this article: Bone Joint Res 2025;14(1):5–15.